Food systems, obesity, and gender in Latin America - Biermayr-Jenzano, Patricia (International Food Policy Research Institute, 2019)
With more than half the population affected by overweight (58%) and almost a quarter (23%) suffering from obesity, Latin America is experiencing an unprecedented health crisis that impacts most of the countries in the region (FAO 2017). Across Latin America, one in four people are obese, and the trend is still critically higher and more prevalent among women than men. The region faces a triple burden of malnutrition, determined by undernutrition, micronutrient deficiency, and overweight and obesity. The topic is very complex, multisectoral, and must be studied from different viewpoints (Allen, de Brauw, and Gelli, 2016; FAO-PAHO, 2016; Gelli et al., 2015; HLPE, 2017; IPES-FOOD, 2016; Townsend, Jaffee, Hoberg, and Htenas, 2016). There is evidence showing that certain groups are more affected, which is the case with women. The impact on other groups and ages varies by country, geographical regions, the urban/rural divide, income and education levels, and ethnic origin. This paper explores the existing linkages connecting the food system, trends in overweight and obesity, and the gender divide in Latin America from the point of view of women, who seem to be disproportionally affected by this health condition than their male counterparts. This literature review explores different dimensions of specific roles and conditions that influence women’s health and nutrition in Latin America, including (a) women as farmers and other affected groups such as indigenous peoples; (b) women’s role and participation in feeding schemes; (c) women as informal street food vendors; (d) women as traders of agricultural products; (e) women as workers in the agrifood industry; and (f) considerations regarding the time invested in food preparation at the household level and women’s participation in this task. Other themes to take into account are the effects of rural poverty and gender inequality on these populations across Latin America and the Caribbean. It is a matter of urgency to understand the underlying causes of some populations’ being more affected by overweight and obesity than others, as this will allow governments to design policies that tackle those problems at their root. The goal of this review is to provide information that can help to develop efficient and equitable interventions and targeted policies to reduce the current trends of overweight and obesity in Latin America.